2021
DOI: 10.3390/cancers13030402
|View full text |Cite
|
Sign up to set email alerts
|

Testing Lab-on-a-Chip Technology for Culturing Human Melanoma Cells under Simulated Microgravity

Abstract: The dynamic development of the space industry makes space flights more accessible and opens up new opportunities for biological research to better understand cell physiology under real microgravity. Whereas specialized studies in space remain out of our reach, preliminary experiments can be performed on Earth under simulated microgravity (sµg). Based on this concept, we used a 3D-clinostat (3D-C) to analyze the effect of short exposure to sµg on human keratinocytes HaCaT and melanoma cells A375 cultured on all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Last year, Przystupski et al [ 192 ] used a novel lab-on-a-chip approach to investigate the effects of short-term s-µ g (RPM) on A-375 human melanoma cells. Their experiments confirmed typical µ g -related morphological (stress fibers, membrane blebbing, lamellipodia, absence of filopodia) and physiological changes (decrease in cell viability and mitochondrial activity, decreased proliferation, and increase in caspase activity) in cells after short-time exposure to s-µ g .…”
Section: Cancer Research In Microgravitymentioning
confidence: 99%
“…Last year, Przystupski et al [ 192 ] used a novel lab-on-a-chip approach to investigate the effects of short-term s-µ g (RPM) on A-375 human melanoma cells. Their experiments confirmed typical µ g -related morphological (stress fibers, membrane blebbing, lamellipodia, absence of filopodia) and physiological changes (decrease in cell viability and mitochondrial activity, decreased proliferation, and increase in caspase activity) in cells after short-time exposure to s-µ g .…”
Section: Cancer Research In Microgravitymentioning
confidence: 99%
“…Recent studies indicate that altered gravity induces shear stresses at the membrane surface, one of the essential factors in sensitizing cancer cells [ 22 ]. Additionally, our previous study showed morphological changes in cancer cells exposed to MG, i.e., stress fibers, membrane blebbing, and cytoskeleton reorganization [ 23 ]. Our study demonstrated that the altered gravity combined simultaneously with cytostatics (here doxorubicin) might be one of the factors modulating the cellular mechanisms and the phenomenon of drug resistance (MDR) in drug-resistant human cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple environmental factors, such as space radiation and microgravity, which can contribute to possibly increasing any risk of tumor development and the possible underlying cellular mechanisms associated with spaceflight [55]. In addition to the studies reviewed in Moreno-Villanueva and Wu [55], more investigations involving microgravity and radiation have been carried out, as shown in Table 3 [56][57][58][59][60][61][62][63] and Table 4 [64][65][66][67][68][69][70][71][72][73], respectively. Although ionizing radiation is a known carcinogen, irradiation with particles in space differs quantitatively and qualitatively from γ-radiation or X-rays [30].…”
Section: Effect Of Space Travel On Cancermentioning
confidence: 99%